2016
DOI: 10.1088/1748-3190/11/4/046007
|View full text |Cite
|
Sign up to set email alerts
|

Optimal flapping wing for maximum vertical aerodynamic force in hover: twisted or flat?

Abstract: This work presents a parametric study, using the unsteady blade element theory, to investigate the role of twist in a hovering flapping wing. For the investigation, a flapping-wing system was developed to create a wing motion of large flapping amplitude. Three-dimensional kinematics of a passively twisted wing, which is capable of creating a linearly variable geometric angle of attack (AoA) along the wingspan, was measured during the flapping motion and used for the analysis. Several negative twist or wash-out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…The cycleaverage horizontal force was approximately 4 mN (≈0.41 gf ), which results in a slightly backward flight of the beetle. Thus, the estimated forces are acceptable to strengthen the accuracy of force estimation by the BET model that was validated in previous papers (Truong et al, 2011;Phan et al, 2016). The power components required to flap and rotate the hindwings are shown in Fig.…”
Section: Force and Power Requirementssupporting
confidence: 66%
See 1 more Smart Citation
“…The cycleaverage horizontal force was approximately 4 mN (≈0.41 gf ), which results in a slightly backward flight of the beetle. Thus, the estimated forces are acceptable to strengthen the accuracy of force estimation by the BET model that was validated in previous papers (Truong et al, 2011;Phan et al, 2016). The power components required to flap and rotate the hindwings are shown in Fig.…”
Section: Force and Power Requirementssupporting
confidence: 66%
“…We used the blade-element theory (BET) model developed in our previous work (Truong et al, 2011;Phan et al, 2016), which is based on 3D wing kinematics as the input condition, to estimate the force generation and power requirement. The force acting on each spanwise section (dr in Fig.…”
Section: Wing Kinematics Analysismentioning
confidence: 99%
“…Many researchers are focusing on flapping-wings in an effort to improve these bio-inspired flyers and move towards bio-mimicked systems through aerodynamic investigations and actuation mechanism optimization [22][23][24]. In addition, a number of researchers have focused on the performance structure of natural and robotic flyers' wings in an effort to further optimize these bio-inspired and bio-mimicked systems [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of this parameter enhances the accuracy of the model while maintaining a lower computational cost than unsteady aerodynamic models. Although some unsteady models may yield better aerodynamic performance predictions, such as Phan et al [42], Parslew et al [43] have shown that the model being used provides sufficient predictions at lower computational costs. In addition, Ghommem et al [44] have validated FlapSim predications with experimental data for a flapping wing NAV (FWNAV), as can be seen in Figure 1.…”
Section: Introductionmentioning
confidence: 99%